2012
DOI: 10.1002/pon.3026
|View full text |Cite
|
Sign up to set email alerts
|

Are psychosocial factors associated with quality of life in patients with haematological cancer? A critical review of the literature

Abstract: Literature about the relationships between psychosocial factors and QoL is lacking. Sense of coherence, self-esteem and health locus of control, coping strategies, social support, global meaning or emotional distress are associated with QoL. Results concerning coping and social support should be interpreted with caution because of level II evidence in studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 43 publications
6
61
1
4
Order By: Relevance
“…Correlates of poorer physical and mental HRQoL among survivors include lack of a partner [15], low socioeconomic status (SES) [15][16][17][18], advanced cancer stage [19,20], invasive or systemic treatments [20,21], shorter time since diagnosis [18], and increased frequency of comorbidities and symptoms [15,[20][21][22]. Age affects each domain of HRQoL differently, with older age negatively correlating with physical HRQoL [18] and younger age negatively correlating with mental HRQoL [15].…”
Section: Introductionmentioning
confidence: 97%
“…Correlates of poorer physical and mental HRQoL among survivors include lack of a partner [15], low socioeconomic status (SES) [15][16][17][18], advanced cancer stage [19,20], invasive or systemic treatments [20,21], shorter time since diagnosis [18], and increased frequency of comorbidities and symptoms [15,[20][21][22]. Age affects each domain of HRQoL differently, with older age negatively correlating with physical HRQoL [18] and younger age negatively correlating with mental HRQoL [15].…”
Section: Introductionmentioning
confidence: 97%
“…Factor help-seeking: Locus of control and coping strategies are associated with QoL in hematological cancer (see review in Allart et al, 2013). In our factor analysis, patients with high internal and low external (powerful others) locus of control were more likely to indicate the wish for support in the Distress Thermometer.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, in other types of cancer, locus of control is the most frequently assessed control beliefs (see review in Neipp, Lopez-Roig, & Pastor, 2007). Indeed, locus of control is associated with QoL in hematological cancer as well (Allart, Soubeyran, & Cousson-Gélie, 2013). Further, cognitive impairments may interfere with reappraisal and thus reduce QoL (Sarkheil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study involving PCP views reported the willingness to accept exclusive care for lymphoma patients was three years after treatment completion [37]. This may be due to the complex nature and length of the treatment regimens [15] and a lack of tumour specific follow-up protocols used by haematologists [35]. With a lack of guidance and comprehensive information communicated from the haematologist [8,35], PCPs may be reluctant to accept exclusive care of what they perceive as complex and 'high risk' patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…Each of these has distinctive and complex treatment regimens that commonly involve aggressive high dose chemotherapy agents, and/or targeted therapies, radiotherapy and haematopoietic stem cell transplants [14]. Unfortunately, the consequence of largely aggressive treatment includes long-term and late physical, practical and psychosocial effects which include: fear of recurrence; fertility; relationship; financial; employment and insurance issues [15][16][17]. A qualitative study on specialist-led follow-up with haematology cancer survivors reported a lack of preparation and support in finding information and resources with poor continuity of care as patients transitioned into the survivorship phase [18].…”
Section: This Has Been Principally Guided By the Institute Of Medicinmentioning
confidence: 99%